2020
DOI: 10.1101/2020.09.29.20201632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial intelligence to predict the risk of mortality from Covid-19: Insights from a Canadian Application

Abstract: The Severe Acute Respiratory Syndrome COVID-19 virus (SARS-CoV-2) has had enormous impacts, indicating need for non-pharmaceutical interventions (NPIs) using Artificial Intelligence (AI) modeling. Investigation of AI models and statistical models provides important insights within the province of Ontario as a case study application using patients' physiological conditions, symptoms, and demographic information from datasets from Public Health Ontario (PHO) and the Public Health Agency of Canada (PHAC). The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Likewise, there is a great variety of studies of this type despite the short time that has elapsed since the pandemic began [ 16 , 41 ]. We can find research around the world about this topic employing IA techniques such as random forest models [ 17 , 42 , 43 , 44 , 45 ], deep learning [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], decision trees [ 43 , 54 ], support vector machine (SVM) [ 49 , 55 ] and logistic regression procedures [ 49 , 56 ]; which are intended to predict the health status (mortality risk or disease severity) of a COVID-19 infected patient employing factors such as the patients age, weight, gender, physiological conditions, demographic data, travel data, computed tomography, vital signs, symptoms, smoking history, radiological features, clinical features, genetic variants, platelets, laboratory test, D-dimer test, chronic comorbidities and general health information. Meantime, other studies [ 57 ] create models using data analysis techniques with the aim of predicting the need of oxygen therapy in a timely manner in COVID-19 patients; which employed variables like shortness of breath, cough, age and fever.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there is a great variety of studies of this type despite the short time that has elapsed since the pandemic began [ 16 , 41 ]. We can find research around the world about this topic employing IA techniques such as random forest models [ 17 , 42 , 43 , 44 , 45 ], deep learning [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], decision trees [ 43 , 54 ], support vector machine (SVM) [ 49 , 55 ] and logistic regression procedures [ 49 , 56 ]; which are intended to predict the health status (mortality risk or disease severity) of a COVID-19 infected patient employing factors such as the patients age, weight, gender, physiological conditions, demographic data, travel data, computed tomography, vital signs, symptoms, smoking history, radiological features, clinical features, genetic variants, platelets, laboratory test, D-dimer test, chronic comorbidities and general health information. Meantime, other studies [ 57 ] create models using data analysis techniques with the aim of predicting the need of oxygen therapy in a timely manner in COVID-19 patients; which employed variables like shortness of breath, cough, age and fever.…”
Section: Introductionmentioning
confidence: 99%
“…An application of different AI models (XGBoost, Neural Network, Random Forest) to predict the possibility of death from COVID-19 compared various population characteristics as features, and the degree to which each feature influences a patient's future mortality (Snider et al, 2020 ). This research found that XGBoost, the same model used in this study, is a reliable method to train COVID-19 cases for death-based predictions, with the highest degree of precision and accuracy (Snider et al, 2020 ).…”
Section: Purposing Ai To Characterize Covid-19: a Reviewmentioning
confidence: 99%
“…Year Accuracy Cohen et al [36] 2020 80% Amer et al [37] 2020 94% Afshar et al [38] 2020 96.24% Borkowski et al [39] 2020 89% Harmon et al [40] 2020 90.8% Snider et al [41] 2020 90.56% Proposed method 2021 91%…”
Section: Studymentioning
confidence: 99%